2015
DOI: 10.3168/jds.2014-9193
|View full text |Cite
|
Sign up to set email alerts
|

Digestive development in neonatal dairy calves with either whole or ground oats in the calf starter

Abstract: A series of 3 trials was conducted to determine effects of whole or ground oats in starter grain on reticulorumen fermentation and digestive system development of preweaned calves. Male Holstein calves (43.1±2.3kg at birth; n=8, 9, and 7 for trials 1, 2, and 3, respectively) were housed in individual pens in a heated facility; bedding was covered with landscape fabric to prevent consumption of bedding by the calves. In trials 1 and 2 only, calves were fitted with rumen cannulas by wk 2 of life. In all trials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
28
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 45 publications
9
28
0
3
Order By: Relevance
“…Total concentration of VFA in the rumen increased with age as has been reported by earlier studies (Greenwood et al, 1997;Beharka et al, 1998;Coverdale et al, 2004). In our previous study (Suarez-Mena et al, 2015), rumen VFA concentration increased with age in a quadratic trend with a small decrease at wk 4, which is somewhat similar to the current study where a plateau was observed between wk 3 and 5 and then an increase at wk 6. The decrease observed in Suarez-Mena et al (2015) and plateau in the current study are likely an effect of greater VFA absorption, because intake increased with time and it is assumed VFA production increases with greater intake.…”
Section: Figuresupporting
confidence: 91%
See 3 more Smart Citations
“…Total concentration of VFA in the rumen increased with age as has been reported by earlier studies (Greenwood et al, 1997;Beharka et al, 1998;Coverdale et al, 2004). In our previous study (Suarez-Mena et al, 2015), rumen VFA concentration increased with age in a quadratic trend with a small decrease at wk 4, which is somewhat similar to the current study where a plateau was observed between wk 3 and 5 and then an increase at wk 6. The decrease observed in Suarez-Mena et al (2015) and plateau in the current study are likely an effect of greater VFA absorption, because intake increased with time and it is assumed VFA production increases with greater intake.…”
Section: Figuresupporting
confidence: 91%
“…Figure 2 illustrates pH variation over time after feeding grain; a nadir was reached at approximately 2 h postfeeding for wk 2 and 6, and at 4 h for wk 1, 3, 4, and 5. The postprandial pH variation is comparable to what we observed in a previous study with similar management (Suarez-Mena et al, 2015). Anderson et al (1987) observed lowest pH values 1 to 3 h postfeeding and a faster recovery to prefeeding values than in the present study; at its nadir average pH was over 5, which was higher than what we observed in the present study.…”
Section: Rumen Fermentation and Digesta Particle Sizesupporting
confidence: 90%
See 2 more Smart Citations
“…However, differences in rumen pH between calves consuming whole or steamed-rolled concentrates may not have been sufficient to provoke changes in straw intake, in part because rumen pH values were >6.0 in both treatments in the present study, in contrast to Lesmeister and Heinrichs (2004), who reported values between 5.4 and 5.8. Suarez-Mena et al (2015) observed only minimal changes in the rumen fermentation profile when offering whole or ground oats from wk 1 to 4 of age, and attributed the lack of difference to the young age of calves. Similarly, in the present study the major changes in rumen fermentation profile were observed at 50 d but not at 35 d. Similar to Beharka et al (1998), in the present study, the butyrate molar proportion increased and branched-chain VFA decreased with time.…”
Section: Discussionmentioning
confidence: 72%